2013
DOI: 10.1111/dgd.12073
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Ca2+ channels maintain a high motility state of the sperm that may be needed for penetration of egg jelly of the newt, Cynops pyrrhogaster

Abstract: Activation state of sperm motility named "hyperactivation" enables mammalian sperm to progress through the oviductal matrix, although a similar state of sperm motility is unknown in non-mammalian vertebrates at fertilization. Here, we found a high motility state of the sperm in the newt Cynops pyrrhogaster. It was predominantly caused in egg jelly extract (JE) and characterized by a high wave velocity of the undulating membrane (UM) that was significantly higher at the posterior midpiece. An insemination assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
(65 reference statements)
0
15
0
Order By: Relevance
“…The binding of the FITC-P3 to the axial rod of the tail was also blocked by the anti-P3 antibody except for that of the principal piece (S2 Fig), thus indicating that the P3 specifically binds to the axial rod of the anterior region of the tail, termed the midpiece. Midpiece is significant for the regulation of sperm motility induced by the SMIS[11]. These results indicate that the obtained cDNA encodes SMIS, whose active site is located at the C-terminal region of the 2nd loop of the CK motif (Figs 1d and 2).…”
Section: Resultsmentioning
confidence: 63%
“…The binding of the FITC-P3 to the axial rod of the tail was also blocked by the anti-P3 antibody except for that of the principal piece (S2 Fig), thus indicating that the P3 specifically binds to the axial rod of the anterior region of the tail, termed the midpiece. Midpiece is significant for the regulation of sperm motility induced by the SMIS[11]. These results indicate that the obtained cDNA encodes SMIS, whose active site is located at the C-terminal region of the 2nd loop of the CK motif (Figs 1d and 2).…”
Section: Resultsmentioning
confidence: 63%
“…A pharmacological study using T-type VDCC blockers, including mibefradil, and L-type VDCC blockers, including nitrendipine, suggests that CaV3.1 or 3.3 of the spermatozoa is involved in the induction of the acrosome reaction by ARIS and CaV3.2 in the initiation of SMIS-induced sperm motility (Takayama-Watanabe et al, 2015). In addition, a nitrendipine-sensitive Ca 2+ channel and a mibefradil-sensitive Ca 2+ channel predominantly mediate the increase of intracellular Ca 2+ to enhance sperm motility in the anterior and posterior midpiece, respectively (Takahashi et al, 2013). The local enhancements are suggested to cause a specific state of motility crucial for spermatozoa to penetrate the jelly matrix.…”
Section: Voltage-dependent Camentioning
confidence: 99%
“…This mechanism is crucial for the internal fertilization of C. pyrrhogaster (Takahashi et al, 2006) and contributes to the initiation of sperm motility inside the female body. The motility is pharmacologically suggested to be mediated by a unique molecular mechanism in which L-type and T-type VDCCs act in distinct sites of the sperm midpiece (Takahashi et al, 2013). In addition, C. pyrrhogaster spermatozoa bind to the vitelline envelope in passing through the jelly layer, though Cynops ZPC, unlike X. laevis ZPC, is suggested not to act as a sperm receptor.…”
Section: Introductionmentioning
confidence: 99%
“…In the sperm of C. pyrrhogaster , intracellular Ca 2+ is increased in both AR induction and motility initiation, as in the sperm of other animal species (Darszon et al 2006 ), and immediately drops down to the initial level (Watanabe et al 2011 ). In addition, we recently found that subsequent infl uxes of Ca 2+ in the motility-initiated sperm cause a high motility state (Takahashi et al 2013 ). Activation of the motility state is needed for sperm to propel through the viscous jelly matrix.…”
Section: Acrosome Reaction-mediated Motility Initiationmentioning
confidence: 99%